An integrative review on the risk factors, prevention, and control strategies for carbapenem-resistant Acinetobacter baumannii colonization in critically ill patients - Zhang, Shihan; Xiao, Jie; Li, Yanan; Li, Wei; Li, Yihui; Pang, Mingmin; Yan, Meichen; Han, Hui; Cui, Yi; Zhang, Xuehai; Wang, Hao (Frontiers in Microbiology, 2025)
The presence of carbapenem-resistant Acinetobacter baumannii (CRAb) has become one of the leading causes of life-threatening, hospital-acquired infections globally, especially with a notable prevalence in intensive care units (ICUs). The cross-transmission of microorganisms between patients and the hospital setting is crucial in the development of CRAb colonization and subsequent infections. Recent studies indicate that colonization typically precedes infection, suggesting the effectiveness and necessity of preventing CRAb colonization as a primary method to lower infection risks. As CRAb infections tend to draw more attention due to their severe symptoms and poor outcomes, understanding the link between colonization and infection is equally vital. To establish a foundation for prevention and control strategies against CRAb colonization in ICUs, we present a comprehensive review of research pertaining to CRAb in ICUs. This encompasses an analysis of the resistance mechanisms and epidemiological characteristics of CRAb, a discussion on associated risk factors, adverse outcomes, and an evaluation of detection methods and preventive strategies.